The Extent and Cyclicality of Career Changes: Evidence for the U.K. - Carlos Carrillo-Tudela; Bart Hobijn; Powen She; Ludo Visschers (Institute for the Study of Labor (IZA), 2014)
Using quarterly data for the U.K. from 1993 through 2012, we document that in economic downturns a smaller fraction of unemployed workers change their career when starting a new job. Moreover, the proportion of total hires that involves a career change for the worker also drops in recessions. Together with a simultaneous drop in overall turnover, this implies that the number of career changes declines during recessions. These results indicate that recessions are times of subdued reallocation rather than of accelerated and involuntary structural transformation. We back this interpretation up with evidence on who changes careers, which industries and occupations they come from and go to, and at which wage gains.
Keywords: J63; J64; G10; 330; labour market turnover; occupational and industry mobility; wage growth